No Single Trajectory : Transnational and Transmedia Explorations of the American West - González, Jesús Ángel,; Sainz, Ángel Chaparro, (European Perspectives on the United States ;, 2024)
This book presents papers by eleven European scholars that explore the ambivalent representations of an American West that follows "no single trajectory, creating instead a series of lines and rhythms, always moving, crossing, and folding" (Neil